Native mRNA editing complexes from Trypanosoma brucei mitochondria. - Pollard, V W (1992)
The aim of this study was to identify multicomponent complexes involved in kinetoplastid mitochondrial mRNA editing. Mitochondrial extracts from Trypanosoma brucei were fractionated on 10-30% glycerol gradients and assayed for RNAs and activities potentially involved in editing, including pre-edited mRNA, guide RNA (gRNA), endonuclease, terminal uridylyltransferase (TUTase), RNA ligase and gRNA-mRNA chimera-forming activities. These experiments suggest that two distinct editing complexes exist. Complex I (19S) consists of gRNA, TUTase, RNA ligase and chimera-forming activity. Complex II (35-40S) is composed of gRNA, preedited mRNA, RNA ligase and chimera-forming activity. These studies provide the first evidence that editing occurs in a multicomponent complex. The possible roles of complex I, complex II and RNA ligase in editing are discussed.